Efektivitas Pembelajaran Blended Learning dalam Pendidikan Agama Kristen Pada Mata Kuliah Public Speaking di STT Kristus Alfa Omega - Pontonuwu, Williyanto (P3M STT Kristus Alfa Omega, 2025)
The main problems faced are low student engagement in the conventional learning process and limited opportunities for effective communication practice. This study aims to analyze the effectiveness of blended learning in improving students' communication competencies, self-confidence, and mastery of theological material. The research method uses a descriptive qualitative approach involving 12 informants, consisting of 1 lecturer and 11 students, through in-depth interviews, classroom observations, and analysis of assignment documents. The results show that the blended learning model provides significant improvements in students' abilities to prepare and deliver Public Speaking materials, expands learning access through the integration of digital platforms, and encourages active participation in theological discussions. The main findings reveal that the combination of face-to-face meetings and online learning strengthens lecturer-student interactions, increases the frequency of speaking practice, and provides a more focused space for spiritual reflection. In conclusion, blended learning has proven effective in the Public Speaking course because it is able to optimize the PAK learning process holistically, relevant to the needs of today's theological education.